Evaluation of hydrological flow for flood mitigation management a case study of Sg Buloh basin, Malaysia / Muhammad Anuar Yusof - Yusof, Muhammad Anuar (2024)
Flood is the natural disaster in msia which contributes up to 90 percent of damage to the country, affecting 4.9 million people every year. The estimated loss suffered in terms of utilities and infrastructure in Malaysia is over RM20 Million, This thesis examines the management of flood mitigation in a basin by considering the losses experienced by residents in the basin, infrastructure, industry, etc. with the benefit of the implementation of the proposed flood mitigation. The objective of this study is to verify hydrological flow from previous studies, predict the cost of damage due to flooding in the study area and propose a suitable flood mitigation plan to reduce the risk of flooding. This research was conducted to study flood prediction (Develop a flood map) and losses in the basin area. The data that needs to be obtained is the Hydrological Flow and will verify the data by carrying out another analysis method, namely the Hydrological Procedure(HP) from the Department of Irrigation and Drainage(DID). Solution methods to overcome flooding will also be suggested by considering the construction cost as optimal. Secondary data will also be taken from past reports such as flood mitigation reports and the Integrated River Basin Management Plan (IRBM). A comparison of the two hydrological flow rates was found to be less than 15% allowing the flow rate data to be used to analyze losses due to flood events. The total amount of losses in the Sg Buloh basin for the 50-year ARI flood condition is RM 58,831,000.00 and the 100-year ARI flood condition is RM 75,120,000.00. The estimated construction cost for the whole is RM 28,544,700.00. Conclusion for estimation cost is flood mitigation construction project in the Sg Buloh basin needs to be carried out to benefit the people in the Sg Buloh basin and the Malaysian Government.